Occupational Trends and Program Priorities - Rosenthal, Dan; Collier, Kitty C. (Education Policy Analysis Archives, 2001)
Institutions of higher education that respond to the economic base in their region will remain competitive and be better positioned to obtain public funds and donor support. In addition to mandated program viability standards based on measures such as graduation rate, individual institutions and state coordinating boards can use ten-year occupational trend data to assess future program viability. We used an occupational demand model to determine whether academic programs can meet projected statewide needs for high demand and high growth occupations. For example, computer engineering, the highest growth rate occupation in Alabama, is projected to have 365 annual average job openings, with 93.6% total growth over ten years. But only 46 computer engineering majors graduate annually from all Alabama institutions of higher education. We recommend using an occupational demand model as a planning tool, decision-making tool, and catalyst for collaborative initiatives.